2009
DOI: 10.1021/ic901246w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Sulfur Oxygenation of a (N3S)Ni Complex Related to Nickel-Containing Superoxide Dismutase

Abstract: A nickel(II) thiolate complex incorporating three N-donor types (amino, amido, and imidazole) has been synthesized and characterized. The (N(3)S)Ni complex, [N-{2-[(2-mercapto-2-methylpropyl)amino]ethyl}-1-methylimidazole-2-carboxamido]nickel(II) (1), is stable in the presence of O(2) but readily forms the sulfinato (RSO(2)(-)) derivative 2 upon the addition of H(2)O(2). Electrochemical investigations of 1 reveal an irreversible sulfur-based oxidation at +0.17 V vs Fc(+)/Fc (200 mV/s) that shifts to +0.81 V up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 29 publications
(73 reference statements)
1
31
0
Order By: Relevance
“…Increasing the energy of the HOMO via an increase in Ni-S covalency in (Ni II (L1)) 2− ( 2 ) effectively activates this species towards electrophiles relative to (Ni II (HL2)) − ( 3 ). These results are consistent with previously reported Ni-SOD model compounds containing mixed amine/amidate Ni II N 2 S 2 coordination that are also air-stable 37,38…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Increasing the energy of the HOMO via an increase in Ni-S covalency in (Ni II (L1)) 2− ( 2 ) effectively activates this species towards electrophiles relative to (Ni II (HL2)) − ( 3 ). These results are consistent with previously reported Ni-SOD model compounds containing mixed amine/amidate Ni II N 2 S 2 coordination that are also air-stable 37,38…”
Section: Discussionsupporting
confidence: 93%
“…Relatively few examples of mixed amine/amidate nickel complexes have been reported as models for Ni-SOD 34–38. Both Shearer34 and others35 have synthesized nickel-peptide complexes as functional models of Ni-SOD.…”
Section: Introductionmentioning
confidence: 99%
“…Questions concerning the enzyme's unusual N/S coordination sphere, particularly its stability toward O 2 and reactive oxygen species (ROS), in light of the reactive Ni–S(Cys) bonds, 13 and the catalytic mechanism have prompted researchers to develop maquette-based, 1420 tripeptide, 2124 and low molecular weight 2538 analogues that seek to replicate NiSOD's structure and/or function. 39,40 Indeed, several experimental and theoretical efforts have suggested that the mixed peptide-N/amine-N ligation serves as one key factor to promote greater Ni-character in the redox-active molecular orbital of NiSOD, in particular for the Ni(II) or NiSOD red state, thus preventing unwanted S-oxidation/oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) Thiolate donors are present in the coordination sphere of metal ions in active sites of metalloproteins [16]; e.g, Fe(II) in peptide deformylase [17], Co (II) in the active site of nitrile hydratase [18], [NiFe]-hydrogenase [19] and metallothioneins containing Zn, Hg, Cd, and Cu [20]. (iii) In the application of certain metalethiolates in medicine, such as Au(I)-thiolates for the treatment of arthritis and triphenylphosphinegold(I) compounds as antitumor agents [21].…”
Section: Introductionmentioning
confidence: 99%